Mothering Sons: Stories by Findley, Hodgins and MacLeod Uncover the Mother's Double Voice - Kruk, Laurie (Atlantis, 2007)
Maternal feminist criticism argues that we are culturally constructed, but also recognizes the embodied experiences of mothers. This maternal "double voice" shifts between subject/object, passive/active and resistant/conforming positions. "Mothering sons" reciprocate the maternal practice of preservation by supporting this "double voice."